(untitled) (International Journal of Engineering and Computer Science, 2015)
The Remote Desktop (RD) paradigm allows end users to remotely access content and applications running on their PCs through a network connection. Remote desktop system uses ARM 32-bit Raspberry Pi micro controller useful for the development of remote virtual desktop services. Raspberry pi board is interface with keyboard, mouse and monitor. Raspberry Pi board setup is interfaced to the PC using LAN connection and communication is done using RDP protocol. To access PC have to use xserver both in PC and Raspberry Pi. Xserver (GUI) is used as interface between user and operating system. Xserver is used to control all actions generated by key board, mouse and gives indication to the system to perform the task. For example if any icon is pressed on the desktop using mouse then it raises event to operating system to perform certain action. Since PC and raspberry Pi both are interfaced through LAN network can be access the desktop using RDP protocol. RDP protocol is remote desktop protocol which is used to read frame buffer from remote desktop and allows displaying the received frame buffer on the monitor connected to Raspberry Pi. Now remote desktop on monitor connected to raspberry pi board. By using keyboard and mouse can be access desktop like opening web browser or entering data on note pad through key board etc.